IDENTIFIKASI BERPIKIR KRITIS MATEMATIKA SISWA KELAS X IPA-6 SMAK SANTO ALBERTUS MALANG - Flavia Aurelia Hidajat; I Nengah Parta; Makbul Muksar (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
This research is meant to identify the critical thinking of X grade students of Science-class in SMAK Santo Albertus, Malang. Data of this research is collected from students test result related to critical thinking test as well as the result of interview done by the researcher with the teacher and students. Data analysis will be done after the treatment and all data are collected. Data analysis technique used in this research is flow model which includes data reduction, data presentation, conclusion and verification. Identification result of students’ critical thinking of X grade in Science-6 class of SMAK Santo Albertus Malang shows that there are three levels in critical thinking, namely ; students with Thinking level of “Critical”, students with thinking level of “less critical”, and students with thinking level of “Not critical”. The result of this research provides information for teachers related to students’ critical thinking, therefore, this research can give some reflection for the teacher in designing the next Mathematics teaching activities and help teacher in designing standard teaching development which improves students’ critical thinking.